Flowering Times of Wild Arabidopsis Accessions From Across Norway Correlate With Expression Levels of FT, CO, and FLC Genes - Kinmonth-Schultz, Hannah; Lewandowska-Sabat, Anna; Imaizumi, Takato; Ward, Joy K.; Rognli, Odd Arne; Fjellheim, Siri (Frontiers in Plant Science, 2021)
Temperate species often require or flower most rapidly in the long daylengths, or photoperiods, experienced in summer or after prolonged periods of cold temperatures, referred to as vernalization. Yet, even within species, plants vary in the degree of responsiveness to these cues. In Arabidopsis thaliana, CONSTANS (CO) and FLOWERING LOCUS C (FLC) genes are key to photoperiod and vernalization perception and antagonistically regulate FLOWERING LOCUS T (FT) to influence the flowering time of the plants. However, it is still an open question as to how these genes vary in their interactions among wild accessions with different flowering behaviors and adapted to different microclimates, yet this knowledge could improve our ability to predict plant responses in variable natural conditions. To assess the relationships among these genes and to flowering time, we exposed 10 winter-annual Arabidopsis accessions from throughout Norway, ranging from early to late flowering, along with two summer-annual accessions to 14 weeks of vernalization and either 8- or 19-h photoperiods to mimic Norwegian climate conditions, then assessed gene expression levels 3-, 5-, and 8-days post vernalization. CO and FLC explained both FT levels and flowering time (days) but not rosette leaf number at flowering. The correlation between FT and flowering time increased over time. Although vernalization suppresses FLC, FLC was high in the late-flowering accessions. Across accessions, FT was expressed only at low FLC levels and did not respond to CO in the late-flowering accessions. We proposed that FT may only be expressed below a threshold value of FLC and demonstrated that these three genes correlated to flowering times across genetically distinct accessions of Arabidopsis.